Torsion of Appendix Case Report - Khattak, Salim; Ali, Arshad (Journal of Postgraduate Medical Institute, 2011)
Mucocele of appendix is a rare presentation, cause being extrisic stricture due to fibrous band or hypertrophy of lymphoid tissues. Distension of appendix due to twist of appendix along its mesentery is extremely rare. The purpose of presenting this case is to bring this on record.